Forensic investigation of ettringite formation in hardened mass concrete structures - Chng, Sebastian Wee Tat (2016)
Ettringite as known as 3CaO•Al2O3•3CaSO4•32H2O( in chemistry abbreviation) which are found in concretes/cement mixtures are classified into two different groups; (Primary Ettringite as known as Type 1) or (Secondary Ettringite as know as Type 2 or Delayed Ettringite Formation DEF). Studies have shown that a certain type of Ettringite to be detrimental and affecting the overall concrete strength in a long period. However, the true identification of the root cause of the development of the Ettringite still remains as a doubt to most researchers. Primary Ettringites that are developed during hydration process have a positive effect as it regulates the settling process during the initial stage of concrete mixing. Hence, the presence of the Primary Ettringite does not create any significant stress to the concrete. In turn, Delayed Ettringite Formation (DEF) which are formed, at the later stage (28 days and beyond) in the concrete are shown to create damage and affecting the strength of the concrete. Hence, the strength of the concrete is unable to be maximise in accordance to its maturity as it projects to be.